2015
DOI: 10.4236/oju.2015.59021
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Fine Needle Aspiration Cytology versus Open Biopsy in the Evaluation of Azoospermic Men

Abstract: Background: Male infertility is a common problem and needs a minimally invasive method to arrive at the appropriate diagnosis. Alternative to open testicular biopsy the fine needle aspiration cytology (FNAC) of the testis is being increasingly used as a minimally invasive method of evaluating testicular function. Aim: To determine the causes of azoospermia and evaluate the efficacy of FNAC as compared to open testicular biopsy in evaluating azoosparmic men by correlating diagnosis from testis FNAC with biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…Infertility is not uncommon health problem in multiple societies & male infertility account for about quarter of the causes of infertility. [9] In this study evaluation of non -obstructive azoospermic males were done by TESA mainly & in 45 cases the TESA were preceded by open surgical biopsy, the most common pattern for spermatogenesis was spermatocytes maturation arrest similar to the results obtained by several studies although none of them use TESA like Al-Dabbgh et al [10] that is carried in Iraq Using testicular FNA for assessment of spermatogenesis & also Khalifa et al [11] , Seo and Ko [12] , Amer et al [13] , and Tusjimura et al [14] . while other studies reported lower frequency of spermatocytes maturation arrest like those carried in Saudi Arabia by Molham M et al [15] & in Jordan by Haddad et al [16] revealed that the most prevalent pattern of spermatogenesis among azoospermic males was normal spermatogenesis followed by hypospermatogenesis putting in our minds that those studies were not excluding patients with Azoospermia due to obstructive causes as in ours, Beside that germ cell maturation arrest may be due to variety of causes like genetic factors or secondary causes such as toxic substances (chemotherapy or radiotherapy), or due to certain chronic renal or liver diseases.…”
Section: Discussionsupporting
confidence: 60%
“…Infertility is not uncommon health problem in multiple societies & male infertility account for about quarter of the causes of infertility. [9] In this study evaluation of non -obstructive azoospermic males were done by TESA mainly & in 45 cases the TESA were preceded by open surgical biopsy, the most common pattern for spermatogenesis was spermatocytes maturation arrest similar to the results obtained by several studies although none of them use TESA like Al-Dabbgh et al [10] that is carried in Iraq Using testicular FNA for assessment of spermatogenesis & also Khalifa et al [11] , Seo and Ko [12] , Amer et al [13] , and Tusjimura et al [14] . while other studies reported lower frequency of spermatocytes maturation arrest like those carried in Saudi Arabia by Molham M et al [15] & in Jordan by Haddad et al [16] revealed that the most prevalent pattern of spermatogenesis among azoospermic males was normal spermatogenesis followed by hypospermatogenesis putting in our minds that those studies were not excluding patients with Azoospermia due to obstructive causes as in ours, Beside that germ cell maturation arrest may be due to variety of causes like genetic factors or secondary causes such as toxic substances (chemotherapy or radiotherapy), or due to certain chronic renal or liver diseases.…”
Section: Discussionsupporting
confidence: 60%